Back Cover: PepSweetener: A Web‐Based Tool to Support Manual Annotation of Intact Glycopeptide MS Spectra. Issue 5 (11th September 2018) - Domagalski, Marcin Jakub; Alocci, Davide; Almeida, Andreia; Kolarich, Daniel; Lisacek, Frédérique
Abstract : The cover represents our software PepSweetener as a link between a raw mass‐spectrometry spectrum and the glycopeptide resulting from its annotation. PepSweetener in fact supports the manual annotation of MS data for intact glycopeptides. It displays an interactive map of all theoretical glycopeptides that match the molecular masses of queried precursor ions. This is reported by Marcin Jakub Domagalski, Davide Alocci, Andreia Almeida, Daniel Kolarich, Frédérique Lisacek in article number1700069 .